Comunicazioni dell'Istituto Papirologico «G. Vitelli» - 13 - Bastianini, Guido; Russo, Simona (Edizioni dell'Istituto Papirologico «G. Vitelli», 2019)
The thirteenth volume of Comunicazioni dell'Istituto Papirologico «G. Vitelli» is divided, as was the previous one, into three sections: 1. Editions and rieditions of texts; 2. Critical notes; 3. Chronique de lexicographie papyrologique de la vie matérielle. In the first section there are texts which are being published for the first time or which are subject to a revision and a new edition, both belonging to various collections. This section also includes the exhibition of an exceptional artefact from the Arab period, belonging to the Papyrological Institute «G. Vitelli»'s collection. The second section includes three contributions with careful palaeographic and linguistic observations on literary and documentary texts, and a fourth contribution offering an exhaustive summary of the publication state of an archive from the Institute's collection. Lastly, the third section, as consolidated by the previous volume of the Comunicazioni, collects several findings of the international research project on the lexicography of material culture (Lex.Pap.Mat.), documented in the language of papyri.